2021
DOI: 10.33507/cakrawala.v5i2.297
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Pembelajaran PAI pada Masa Pandemi di SMK Ma’arif 1 Kebumen Tahun 2020/2021

Abstract: Agus Salim Chamidi, Fiqri Khofifah, Fita Lestari, Hesti Nurwindiasih, Khofifatun Sholikhah, Luthfiy Atiqoh, Mohamad Affan Sobri, Nadhirotul Munawaroh, Umi Salamah, Wahid Wildah Hidayat, Sri Wahyuni, Asfi Ngamalia Hasanah  Abstrak Riset kolaboratif dosen mahasiswa ini bertujuan untuk mengetahui manajemen pembelajaran Pendidikan Agama Islam (PAI) pada masa pandemic covid19 di SMK Maarif 1 Kebumen, kendala yang muncul, dan langkah solutifnya. Penelitian merupakan penelitian kualitatif dengan menggunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The data analysis process employs qualitative data analysis using the interactive model according to Miles and Huberman, as explained by Harfiani (2021). The interactive data analysis technique consists of four components in the analysis process: data collection, data reduction, data presentation, and drawing conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…The data analysis process employs qualitative data analysis using the interactive model according to Miles and Huberman, as explained by Harfiani (2021). The interactive data analysis technique consists of four components in the analysis process: data collection, data reduction, data presentation, and drawing conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…IRE learning management has progressed when a pandemic hits the world. The results of research on IRE learning management during the pandemic showed that teachers' and facilities' creativity must support the learning process (Chamidi, 2021;Solong, 2021).…”
Section: Introductionmentioning
confidence: 99%